Egg Consumption and Risk of Heart Failure in the Physicians' Health Study - Djoussé, Luc (2008)
BACKGROUND: Reduction in dietary cholesterol is widely recommended for the prevention of cardiovascular disease. Although eggs are important sources of dietary cholesterol and other nutrients, little is known about the association between egg consumption and heart failure (HF) risk. METHODS AND RESULTS: In a prospective cohort study of 21,275 participants from the Physicians' Health Study I, we examine the association between egg consumption and the risk of HF. Egg consumption was assessed using a simple abbreviated food questionnaire and we used Cox regression to estimate relative risks of HF. After an average follow up of 20.4 years, a total of 1,084 new HF cases occurred in this cohort. While egg consumption up to 6 times per week was not associated with incident HF, egg consumption of 7 or more per week was associated with an increased risk of HF. Compared to subjects who reported egg consumption of < 1 per week, hazard ratios (95% CI) for HF were 1.28 (1.02-1.61) and 1.64 (1.08-2.49) for egg consumption of 1/day and 2+/day, respectively, after adjustment for age, body mass index, smoking, alcohol consumption, exercise, and history of atrial fibrillation, hypertension, valvular heart disease, and hypercholesterolemia. Similar results were obtained for HF without antecedent myocardial infarction. CONCLUSIONS: Our data suggest that infrequent egg consumption is not associated with the risk of HF. However, consumption of 1 or more eggs per day is related to an increased risk of HF among US male physicians.